Genealogical Links in Samogitian Nobility Heraldry Sources in the Second Half of the 16th–18th Centuries - Jasiūnienė, Gabrielė (Bibliotheca Lituana, 2019)
Heraldry and its research have deep traditions in Europe, making it a certain focus of attention among researchers. The interest in this field in Lithuania is a more recent phenomenon. The late beginning of heraldry research was partly influenced by Lithuania’s loss of independence. At present, researchers’ attention is focused mainly on the periods of the Grand Duchy of Lithuania and the Polish-Lithuanian Commonwealth, also looking at Lithuanian heraldry from the 20th–21st centuries, and conducting thorough research of the coats of arms of the state, cities, and towns. Research of the heraldry of the nobility is also being conducted, such as the heraldry of the political elite in the Grand Duchy of Lithuania – the Goštautas, Pacas, Radvila, Sapiega families, etc. The heraldry of representatives of the lower gentry, especially among the Samogitian families, has received less attention. Many unanswered questions and undeveloped themes remain in the field of the Samogitian nobility’s heraldry, overlooked in research for a long time. This article analyzes how genealogical links were reflected in Samogitian nobility heraldry sources in the second half of the 16th–18th centuries. Having analyzed the heraldic sources of the Samogitian nobility, it was found that these reflected not only information about a specific individual, but also their broader origins, family and marital lines. The coats of arms of the Samogitian nobility in time became a unique means of representation. The coats of arms of the Samogitian nobility were depicted in seals, literature, portraits, architecture, and elsewhere.